Perbedaan Metode Drill dan Metode Bagian (Part-Whole) Terhadap Teknik Renang Gaya Bebas Bagi Perenang Pemula - Salman Yega; Dinar Dinangsit; Entan Saptani (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to determine the differences in the improvement of 25-meter freestyle swimming speed between beginner swimmers trained using the drill method and those trained using the part-whole method, as well as to identify the more effective method for improving freestyle swimming performance. The method used was a quantitative study employing a quasi-experimental approach with a Two Group Pretest-Posttest Design. The participants consisted of 30 beginner swimmers who were divided into two groups, namely the drill group (n = 15) and the part-whole group (n = 15). The research instrument was a 25-meter freestyle swimming test in which swimming time was measured using a stopwatch. Data were analyzed using the Independent Sample t-test. The results showed that the drill group demonstrated an average improvement of 4.01 seconds, whereas the part-whole group showed an average improvement of 3.11 seconds. The posttest Independent Sample t-test yielded a significance value of 0.076 (p > 0.05), indicating that there was no statistically significant difference between the two groups. However, descriptively, the drill method produced greater improvements in swimming speed than the part-whole method. In conclusion, both the drill method and the part-whole method were effective in improving the 25-meter freestyle swimming speed of beginner swimmers. Nevertheless, the drill method tended to be more effective in enhancing freestyle swimming performance. Keywords: Beginner Swimmers, Drill Method, Freestyle Swimming, Part-Whole Method, Swimming Speed